DETECTIVE STORY: TO THE PROBLEM OF VARIABILITY OF THE MAIN EVENT AND CHARACTERS (BY THE CASE OF A. SARAKHOV’S STORIES) - I. A. KAZHAROVA (Кавказология)
The article discusses aspects of the development of detective prose, necessary for understanding the status of a detective in Kabardian literature. The functionality of stereotypes of perception and «memory of the genre» is briefly presented, which manifests itself in the history of understanding a domestic detective story as a constant appeal to the foreign sources of the genre. The reasons for the detective’s unpopularity in Kabardian literature, the role of mental attitudes and their connection with the peculiarities of the history of written culture are examined. The material of the novels «The Case is Tobacco», «Card Debt» and «Ebarg» by the contemporary writer A.A. Sarakhov show the most noticeable features that individualize the genre of “police detective” in the work of a particular author. In this case, they turn out to be the variability of the main event and the characters. The lack of scientific works devoted to the genre of the detective in Kabardian literature and the work of A.A. Sarakhov determines the relevance of the presented study.